Interfacial Design for a 4.6 V High‐Voltage Single‐Crystalline LiCoO2 Cathode. Issue 8 (18th January 2022) - Zhang, Jiaxun; Wang, Peng‐Fei; Bai, Panxing; Wan, Hongli; Liu, Sufu; Hou, Singyuk; Pu, Xiangjun; Xia, Jiale; Zhang, Weiran; Wang, Zeyi; Nan, Bo; Zhang, Xiyue; et al.
Abstract: Single‐crystalline cathode materials have attracted intensive interest in offering greater capacity retention than their polycrystalline counterparts by reducing material surfaces and phase boundaries. However, the single‐crystalline LiCoO2 suffers severe structural instability and capacity fading when charged to high voltages (4.6 V) due to Co element dissolution and O loss, crack formation, and subsequent electrolyte penetration. Herein, by forming a robust cathode electrolyte interphase (CEI) in an all‐fluorinated electrolyte, reversible planar gliding along the (003) plane in a single‐crystalline LiCoO2 cathode is protected due to the prevention of element dissolution and electrolyte penetration. The robust CEI effectively controls the performance fading issue of the single‐crystalline cathode at a high operating voltage of 4.6 V, providing new insights for improved electrolyte design of high‐energy‐density battery cathode materials. Abstract : Single‐crystalline cathode materials have attracted intensive interest. However, the single‐crystalline LiCoO2 suffers severe structural instability and capacity fading when charged to high voltages (4.6 V vs Li/Li + ) due to Co and O element dissolution, crack formation, and electrolyte penetration. In this work, the above problems are inhibited by forming a robust cathode electrolyte interphase (CEI) on the surface of LiCoO2 .